The Influence of Nano Bentonite Filler Material and Cyclic Natural Rubber Grafted Oleic Acid as a Compatibilizer on the Blend of Cyclic Natural Rubber/Polyamide - Aritonang, Barita; Ritonga, Ahmad Hafizullah; Harefa, Karnirius (Formosa Journal of Sustainable Research, 2024)
Cyclic natural rubber (CNR) and polyamide (PA) cannot blend homogeneously due to their differing polarities. CNR is nonpolar with low surface tension, while PA is polar with high surface tension. To achieve a homogeneous and compatible CNR/PA blend, a CNR-g-OA compatibilizer is required. This study aims to investigate the influence of CNR-g-OA and nano bentonite on the physical and chemical properties of the PA/CNR mixture. The research findings indicate successful grafting of OA onto CNR, resulting in CNR-g-OA formation. Based on electron microscope structural analysis, the CNR/PA mixture yields a homogeneous and compatible blend. In conclusion, CNR-g-OA and nano bentonite can enhance the quality of the PA/CNR blend by producing a homogeneous and compatible mixture